Growth of Asian pension assets: Implications for financial and capital markets - Yuwei Hu (Asian Development Bank Institute (ADBI), 2012)
Pension assets have seen rapid growth world-wide over the past decades, although they suffered large losses during the global financial crisis of 2007 - 2008. Such growth is notably due to both structural and parametric pension reforms since the 1980s. In the Asian region too, the pension market has steadily expanded. This paper seeks to identify the impact of Asian pension funds on selected key transmission mechanisms from pension reform to financial development. Utilizing a panel error correction model, we found a statistical relationship between pension asset growth and development of financial and capital markets. The main policy implication is that governments in Asia should continue and/or strengthen pension reforms towards more pre-funding of future liabilities, since it brings beneficial impacts on the financial market.
Keywords: G23; G28; C54; 330; asia; pension systems; asian pension funds; pension reform; Pensionskasse; Kapitaleinkommen; Anlageverhalten; Rentenreform; Finanzmarktregulierung; Finanzkrise; Asien